Analisis Kinerja Perangkat Desa di Kabupaten Lumajang - Setyobakti, Moh. Hudi; Murniati, Wahyuning (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
Village apparatus is an important factor in the running of the government process in the village. Therefore an analysis is needed to determine the factors that affect the performance of the village apparatus. There are two independent variables in this study, namely; work ethic and work discipline. In the process this study uses village tools in Lumajang District as a population with 64 respondents. Furthermore, for data analysis techniques using multiple linear regression analysis, the results of the analysis show that both work ethic and motivation have a significant effect on the performance of the village apparatus. This is supported by the coefficient of determination of 73.4% so that only 26.6% remains for other variables that affect the performance of village equipment. This research is expected to contribute to the development of studies in management science, especially human resource management so that it can become a reference to further research.